Dequalinium Chloride Effectively Disrupts Bacterial Vaginosis (BV) Gardnerella spp. Biofilms - Carlos Gaspar; Joana Rolo; Nuno Cerca; Rita Palmeira-de-Oliveira; José Martinez-de-Oliveira; Ana Palmeira-de-Oliveira (Pathogens, 2021)
Bacterial vaginosis (BV) is the most frequent vaginal infection worldwide. It is caused by the overgrowth of anaerobic vaginal pathogens such as Gardnerella spp. BV has been associated with the occurrence of dense multispecies biofilms on the vaginal mucosa. Treatment of biofilm-associated infections such as BV is challenging. In this study, we have tested the role of a quaternary ammonium compound, dequalinium chloride (DQC), in the eradication of Gardnerella spp. biofilms. The effects of the test substance on the biomass and the metabolic activity of the biofilm of Gardnerella spp. were assessed in vitro using a microtiter plate assay. In addition, the effect of DQC on the Gardnerella spp. biofilm was further assessed by using scanning electron microscopy and confocal laser scanning microscopy. The results showed that DQC was particularly effective in the destruction of BV-associated Gardnerella spp. biotypes, impacting both their biomass and metabolic activity. In addition, the disruption of biofilm architecture was evident and was probably caused by multiple mechanisms of action. We conclude that DQC is an antibiofilm agent and is able to efficiently destroy Gardnerella spp. BV-associated biofilms. Therefore, it is a valid option for BV therapy and has the potential to prevent BV recurrences.